2019
DOI: 10.1002/term.2848
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐tricalcium phosphate ceramic triggers fast and robust bone formation by human mesenchymal stem cells

Abstract: Due to their osteoconductive and inductive properties, a variety of calcium phosphate (CaP) scaffolds are commonly used in orthopaedics as graft material to heal bone defects. In this study, we have used two CaP scaffolds with different hydroxyapatite (HA) and β‐tricalcium phosphate (β‐TCP) ratios (MBCP®; 60/40 and MBCP+®; 20/80) to investigate their intrinsic capacity to favour human bone marrow stem cells (hBMSCs) osteogenic differentiation capacity. We report that MBCP+® showed in in vitro culture model a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…There were many clinical studies from MBCP which consists with 60% of HA and 40% of β-TCP78798081828384. On the other hand, MBCP+ was published only animal studies85868788 and in vitro studies8990. Although not introduced as MBCP+, a combination of 20% of HA and 80% of β-TCP was as same resorption and bone growth as combination of 60% of HA and 40% of β-TCP in retrospective clinical trial for extraction socket and it could be human study level IV84.…”
Section: Resultsmentioning
confidence: 99%
“…There were many clinical studies from MBCP which consists with 60% of HA and 40% of β-TCP78798081828384. On the other hand, MBCP+ was published only animal studies85868788 and in vitro studies8990. Although not introduced as MBCP+, a combination of 20% of HA and 80% of β-TCP was as same resorption and bone growth as combination of 60% of HA and 40% of β-TCP in retrospective clinical trial for extraction socket and it could be human study level IV84.…”
Section: Resultsmentioning
confidence: 99%
“…After these results obtained in vitro, the osteogenic potential of CPCs was assessed in vivo. CPCs, combined with the osteoinductive ceramic granules, as described by Pereira et al [45], formed a compact fibrous tissue, virtually ascribable to an immature bone-like matrix, 2 months after implantation in mice ( Figure 6C). Altogether, these data demonstrated that CPCs were preferentially committed to a stable chondrogenic fate, a feature that is crucial for cartilage regeneration purposes and make CPCs a better option than traditional MSCs, usually predetermined to develop from transient endochondral cartilage to bone [46].…”
Section: Cpcs-pl Produced Hyaline-like Cartilage In Vivo Suitable Formentioning
confidence: 69%
“…With the development of an understanding of the reactions between biomaterials and host tissues, the regulatory effect of the immune system on biomaterial-induced osteogenesis has gradually become a focus of study [ 20 , 21 ]. To date, most studies have mainly identified the direct osteoinductive effect of Zn 2+ [ 8 , 22 ] or β-TCP [ 23 , 24 ] on host/exogenous stem cells. Whether and how the Zn/TCP/PLLA scaffold regulates the local osteoimmune microenvironment around the bone defect area remains unknown.…”
Section: Introductionmentioning
confidence: 99%